Finding a model for contrastive lexical semantics: A look at verbal communication verbs - Viberg, Åke (LingBaW. Linguistics Beyond and Within, 2017)
A basic problem for contrastive lexical studies in general is to find a model for the semantic analysis. This paper is one in a series of corpus-based contrastive studies of the field of Verbal Communication Verbs (VCVs) in English and Swedish. Searle’s classification of speech acts serves as an important starting point but is not directly concerned with lexical structure, which is a major concern for the two theories that are compared in this study. FrameNet based on Fillmore’s theory of semantic frames and Wierzbicka’s theory of semantic primitives (or “primes”). The theories are applied and tested on data from the English Swedish Parallel Corpus (ESPC) containing English and Swedish original texts together with their translations into the other language. Primarily two groups of English verbs and their Swedish correspondents will be analyzed: (1) Information verbs such as tell, inform, notify, report, narrate and describe and (2) Speech activity verbs such as talk, speak, chat, converse, gossip, discuss, debate, negotiate and bargain. There is also an analysis of Swedish berätta ‘tell, narrate’ based on the Multilingual Parallel Corpus (MPC) as an example of multilingual contrastive analysis. Frames relate in a clear way the conceptual structure and the syntactic argument structure, which is very useful in a contrastive study. However, the definition of the meaning of individual verbs is incomplete and needs to be complemented with some kind of decompositional analysis such as the theory of semantic primes. A special section is devoted to an analysis of a large number of compound and derived forms of the Swedish verb tala ‘speak’ and a discussion of how contrasts in morphological structure can affect the lexical contrasts between two languages.